The Antipode of the True as a Contrary Concept of the True - Hakobyan, Gevorg (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The article deals with the interpenetrating relationships between the essences of the characteristics opposite to the true, highlighting the central role of disclosure and determining the possible contrary of the true. From the discussion it turns out that in the scientific-philosophical discourse there is no agreement on the essence of the opposite characteristics of the true and as opposites to true many characterizations are used to reflect exactly the same gnoseological qualification; (among others) wrong, false, lie, aberration, antitruth, etc. Therefore, in scientific-philosophical Armenian-language literature (textbook, article, monography) there is no agreement as in what sense and in what cases each of these concepts should be applied. Taking into account the circumstance that the concepts which are opposite to the true have an essential role in the process of cognition, the article proposes to demarcate the limits of the usage of these concepts and to cancel the tradition of their equivalent usage. Especially since there are such mental structures that are beyond the true/false (wrong, lie, aberration, etc.) logical-gnoseological dimension. In this context it also turns out that the absence of this agreement has objective grounds, the most important of which is the absence of a concept and a word that accurately reflects and expresses the idea of "contrary to the true." Therefore, it is proposed to solve the problem by accepting conditional consensuses, including by reflecting the idea "contrary to the true" with the concept of the antipode of the true.